QUALITY OF LIFE OF SENIORS LIVING IN COMMUNITY SETTINGS - Farský, Ivan; Solárová, Michaela (Profese Online, 2010)
Aim:The purpose of this study was to assess quality of life in elderly in institutionalized community care.Methods:All participants completed WHOQOL-BREF scale. Study sample consisted of 40 subjects. There were 20 women (mean age 75.7±4.9 ys.) and 20 men(mean age 74.7±5.6 ys.) in the group.Results:The seniors had average level of quality of life. The lowest scored domain of quality of life was physical domain. Evidently better were scored domains Environment and Psychological health. Seniors had the best score in Social domain.Conclusion:These findigs we can use as a starting-point for planning and realization of changes in health and social care of elderly in community care.
Keywords: quality of life; elderly; WHOQOL-BREF; community care